1989
DOI: 10.4319/lo.1989.34.4.0700
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐lake experiments: The annual record of fossil pigments and zooplankton

Abstract: The annual record of fossil pigments and zooplankton was compared with detailed contemporaneous records from two manipulated lakes from 1940 to 1986. Annually resolved sedimentary records accurately monitored known changes in plankton communities, identified periods of trophic change, and proved a powerful tool for examining long-term, complex interactions. Both Paul and Peter Lakes underwent the same three complete changes in their fish assemblages (trout, cyprinid, bass), and Peter Lake received repeated inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
149
0
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(158 citation statements)
references
References 39 publications
(67 reference statements)
7
149
0
2
Order By: Relevance
“…G ST values were lower than 0.022 in both cases (Fig. 4) (24,25). The strong fit between the egg-density profile and inferred fish predation pressure supports the notion that the Oud Heverlee sediment record is intact and not disturbed at either of our core sites.…”
Section: Resultssupporting
confidence: 68%
“…G ST values were lower than 0.022 in both cases (Fig. 4) (24,25). The strong fit between the egg-density profile and inferred fish predation pressure supports the notion that the Oud Heverlee sediment record is intact and not disturbed at either of our core sites.…”
Section: Resultssupporting
confidence: 68%
“…In contrast, several other aquatic studies have shown that alloxanthin (cryptophytes) can dominate carotenoid concentrations in surface sediments (Repeta & Gagosian 1987;Leavitt et al 1989;Hurley & Armstrong 1991). Goebel (2001) described a maximum of cryptophytes in the LSL just outside Deep Cove, which is supported by the elevated alloxanthin concentrations in the sediment traps at this site.…”
Section: Diatoms Dominate Plankton Remainsmentioning
confidence: 74%
“…In designing tests for these ideas, we have favored an experimental approach (Carpenter 1988a;Carpenter and Kitchell 1988;Carpenter et al 199 1). Paleolimnological reconstructions (Kitchell and Carpenter 198 7;Leavitt et al 1989;Carpenter and Leavitt 199 l), longterm records (Mills et al 1987;Jassby et al 1990), and multilake comparative studies (Mills and Schiavone 1982;Pace 19 84;Carpenter et al 199 1) have also provided valuable evidence. Since DeMelo et al restrict their scope to experiments, we will not address other research approaches in our comment.…”
Section: Commentmentioning
confidence: 99%
“…Evidence of those effects will typically take more time than the duration of most experiments. Recent results of paleolimnological studies offer confirmation of lag effects and the encouragement of an approach that can serve as a surrogate for longterm studies (Leavitt et al 1989;Carpenter and Leavitt 199 1).…”
Section: Commentmentioning
confidence: 99%